From clues to conclusion: using ‘a bloody reunion’ to enhance inferring skills among university EFL learners - Shafie, Bukhari; Selvakumaran, Yamunna; Hashim, Harwati; Md Yunus, Melor (Human Resource Management Academic Research Society, 2024)
Critical thinking skills are imperative in a 21st-century classroom. One of the ways to foster critical thinking skills is through the mastery of inferring strategy. Inferring is a method used to generate a useful conclusion by presenting evidence and facts. Marzano (2010) asserted that inferring is a ‘foundational skill’ that is essential for higher-order thinking. In order to cultivate inferring skills, A Bloody Reunion: A Murder Mystery Game is developed to place students in an environment where critical thinking is utilised at the optimum level. Before students are engaged with the murder mystery game, they are first given a pre-game activity focusing on understanding contextual clues. Mastering contextual clues can tremendously train effective inferring. After that, students are given a text that revolves around finding out who the murderer is based on the evidence found. This game was tested on three EFL students of CEFR B1 proficiency at an international university in Gombak, Malaysia . The findings from the interview conducted show that the game helps to foster inferring skills tremendously. Therefore, this murder mystery game can help teachers groom higher-order thinking skills among students by specifically tapping on inferring skills